2017
DOI: 10.1515/reveh-2016-0054
|View full text |Cite
|
Sign up to set email alerts
|

Linking childhood allergic asthma phenotypes with endotype through integrated systems biology: current evidence and research needs

Abstract: Abstract Asthma and other complex diseases results from a complex web of interactions involving inflammation, immunity, cell cycle, apoptosis, and metabolic perturbations across multiple organ systems. The extent to which various degrees of the age at onset, symptom severity, and the natural progression of the disease reflect multiple disease subtypes, influenced by unique process of development remains unknown. One of the most critical challenges to our understanding stems fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 80 publications
(125 reference statements)
0
4
0
Order By: Relevance
“…In systems biology, large data sets collected by multiple modalities in populations, ideally with multiple dimensions of data for each individual, are used to generate networks that link phenotyping information to interdependent genetic, regulatory, metabolic, and environmental profiles. The resulting networks are used to predict behavior of the trait and generate novel, biologically relevant information [74].…”
Section: Big Datamentioning
confidence: 99%
“…In systems biology, large data sets collected by multiple modalities in populations, ideally with multiple dimensions of data for each individual, are used to generate networks that link phenotyping information to interdependent genetic, regulatory, metabolic, and environmental profiles. The resulting networks are used to predict behavior of the trait and generate novel, biologically relevant information [74].…”
Section: Big Datamentioning
confidence: 99%
“…Genomic systems biology approaches – defined as those that take a holistic approach to disease understanding informed by multiple disciplines, genomics, and bioinformatic data sources(13, 14) – have previously been effective at identifying biological processes contributing to the etiology of complex genetic diseases. (15, 16) Here, we take a systems approach to address the genomics of ICS response in individuals with asthma, building on our previous Bayesian-network based methodology, Reverse Engineering and Forward Simulation (REFS). (17) This method uses patient genomic and outcome data to identify genes driving the associations of interest, enriching for likely causal importance of such associations.…”
Section: Introductionmentioning
confidence: 99%
“…In the last 2 years, several studies and reviews have sought to link allergic disease phenotypes and endotypes with potential targets for treatment in a precision medicine approach . In January 2017, the PRACTALL group published a summary on the potential for precision medicine in allergic disease, which concluded that while some progress has been made in defining endotypes for allergic disease and identifying biomarkers to guide a precision medicine approach to treatment, further validation and quantification of these biomarkers are needed to allow their translation into practice in the clinical management of allergic disease …”
Section: Advances In Allergen Immunotherapymentioning
confidence: 99%